Hubungan Antara Beban Kerja dan Coping Stress pada Mahasiswa yang Bekerja Secara Part Time - Annisa Warastri; Mega Sri Rahayu (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Studying and working are familiar things to encounter nowadays, if you look at the many universities in Indonesia, both public and private, that provide special classes for employees. This phenomenon as a trend chosen by female students is currently motivated by various reasons, for example the problem of financing education or daily needs, to fill free time, or as an option for wanting to live independently so that they are not dependent on their parents for their lives and at the same time being able to lighten the family's burden. Interestingly, among students, most of them are interested in part-time work on the grounds that it is more flexible compared to full-time work, so that students can adjust work schedules and study schedules. Of course, studying and working is not easy because students spend a lot of time studying or just doing assignments from lecturers. The impact of this on students can disrupt learning activities, and judging from the possibility that many students are negligent in carrying out their assignments and it is feared that these students' preoccupation with work will override lectures and their studies will be neglected or even drop out. In carrying out study activities while working, stress coping is needed to handle the workload received, because there is pressure from workload and stress when studying while working. The aim of this research is to look at the relationship between workload and stress coping in students who work part time. This research uses quantitative methods with a correlational approach. There were 96 respondent data collected for processing. Data collection using workload and stress coping scales via Google Forms. The results of the analysis show results (0.008  0.05), meaning that there is a relationship between workload and stress coping in students who work part time. That the higher the perceived workload, the more stress coping behavior will be carried out.